POWER QUALITY ASSESSMENT AND MITIGATION AT WALYA-STEEL INDUSTRIES AND ETHIO-PLASTIC SHARE COMPANY - Mamo, Mengesha; Merid, Adefris (Zede Journal of Ethiopian Engineers and Architects, 2023)
In this paper, electric power quality (PQ) in Walya- Steel Industries PLC (WSIPLC) and Ethio-Plastic Share Company (EPSC), which are customers of Ethiopian Electric Power Corporation (EEPCo), are studied. PQ indicators of the two industries are recorded and analyzed. The study demonstrated that harmonic distortion is high relative to the corresponding IEEE recommended maximum permissible values while power factor of the two factories’ power systems are low. Other PQ indicators are within the range of allowable values. The simulation done on the modeled power system of the two factories demonstrates that major source of harmonic distortion is power electronic converters, which are in use in both factories. Based on the simulation results, capacitive filter for the harmonic distortion and low power factor mitigation have been designed